A randomized controlled trial on the effect of smartphone-based mental health application among outpatients with depressive and anxiety symptoms: A pilot study in Malaysia - Sharon Tan; Mohammad Ayob Bin Ismail; Tuti Iryani Mohd Daud; Rozita Hod; Norfazilah Ahmad (Indian Journal of Psychiatry)
Introduction: Despite the increasing number of mental health professionals in Malaysia, many have yet to receive adequate treatment for common mental illnesses such as depression and anxiety. Coupled with the increasing number of mobile phone users globally, smartphone-based intervention can be a promising mental health intervention. Thus, this study aims to investigate the efficacy of using a smartphone-based mental health application in addition to treatment-as-usual (TAU) in outpatients with depressive and/or anxiety symptoms. Methods: Psychiatric outpatients that fulfill the selection criteria were recruited and randomized into two groups, the intervention group (n = 24) and the control group (n = 24). Those in the intervention group received MoodMission in addition to TAU, while those in the control group received TAU. Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder-7 (GAD-7) scores were assessed at baseline and after four weeks. Results: A total of 48 participants were recruited, randomized, and completed the study. Baseline characteristics for both groups were comparable. There is no significant mean difference between-group comparison of PHQ-9 (1.31, 95% CI -1.35, 3.98) and GAD-7 (0.02, 95% CI -2.01, 2.05) scores at four weeks. However, for the intervention group, there was a significant improvement in the PHQ-9 score at four weeks [mean difference 2.58 (95% CI 1.16, 4.01), P = 0.001)]. Conclusion: This study showed no significant improvement in anxiety symptoms after four weeks. Use of smartphone-based mental health applications led to significant reduction of depressive symptoms.